Perfil da pobreza no Brasil e sua evoluç\~ao no período 2004-2009 - Rafael Guerreiro Osorio; Pedro H. G. F. de Souza; Sergei S. D. Soares; Luis Felipe Batista de Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This text investigates, for 2004 and 2009, the characteristics and living conditions of four demographic categories defined by household per capita income values. These are the extreme poor (those whose per capita incomes were less than R 67 in 2009), the poor (between R 67 and R 134), the vulnerable to poverty (between R 134 and R 465) and the non-poor (per capita incomes greater than R 465). We investigate the size of each group, its labor market insertion, demographic characteristics, educational attainment, geographical distribution, as well as various characteristics of the house they live in. We also present a classification of types of family most likely to be found in extreme poverty. Our first conclusion is that, in spite of the strong reductions in the number of poor, the relative geographical, age, racial, and educational distribution of poverty has not changed much between 2004 and 2009. Our second conclusion is that the most important changes in poverty were a result of: i) inclusive growth through the labor market; ii) real increases in the minimum wage which have all but eradicated extreme poverty and even non-extreme poverty among families counting on at least one elderly person; iii) increases in coverage and benefits of targeted cash transfers that were for many families with at least some labor income the escape route from extreme poverty and even poverty.
Keywords: I32; 330; Armut; Haushaltseinkommen; Brasilien